Pengaruh Profitabilitas, Ukuran Perusahaan, Struktur Kepemilikan, Leverage, dan Umur Perusahaan Pada Ketepatan Waktu Pelaporan Keuangan - Valentina, I Gst Ayu Putu Bunga; ., Gayatri (E-Jurnal Akuntansi, 2018)
Timeliness in the presentation of financial statements to the public is needed and therefore each company is expected not to postpone the presentation of financial statements. One way to measure transparency and quality of financial reporting is timeliness, time span between the date of the company report and the date when financial information is publicly disclosed relates to the quality of the financial information reported. Timely delivery of financial statements is one of the important characteristics in supporting the relevance of financial information. Information has the potential to lose its relevance due to age and extension of time delay in the presentation of financial statement information, thus becoming less useful information for economic decision making. The purpose of this study is to analyze the effect of profitability, firm size, ownership structure, leverage, and firm age on timeliness of reporting Finance. The research population is all bank companies registered in BEI for the period of 2012-2016 which totals totaling 43 bank companies, and samples in the research that meet the criteria selected in the sample determination are 28 companies with the total sample during the period 2012-2016 as many as 140 companies. Analytical techniques in this study using logistic regression Based on the results of the analysis found that profitability and leverage does not affect the timeliness of financial reporting while firm size, ownership structure and age of the company have a positive effect on timeliness of financial reporting. This proves that profitability, firm size, ownership structure, leverage and age of the firm can affect the timeliness of financial reporting. Keywords : profitability, firm size, ownership structure, leverage, age of company and timeliness of financial reporting.